Geographical Distribution of Sustainable Tourism Development of the Countries of the European Union Using the Machine Learning Method - Josef BOTLÍK; Milena BOTLÍKOVÁ; Petr JANÍK; Jana STUCHLÍKOVÁ (Communications of International Proceedings, 2020)
On the one hand, the long-term growth of tourism leads to the development of the environment. The mass nature of tourism in recent years has created negative pressures on the social and natural environment. For these reasons, development needs to be geared towards sustainability. Creating an environment in which social, economic and environmental areas are consistent. Measuring the sustainability of tourism in the EU is based on the methodology of European indicators for assessing sustainable development. The article deals with the comparison of sustainable tourism of EU countries on the basis of selected indicators from individual areas of sustainability year-on-year comparison of 2012 and 2017 through machine learning methods and comparative analysis. The results show that there are countries that are still lagging behind in achieving sustainability goals in terms of renewables or waste production.
Keywords: Sustainable; tourism; environment; European Union.